Folic Acid-Conjugated pH and Redox-Sensitive Ellipsoidal Hybrid Magnetic Nanoparticles for Dual-Triggered Drug Release - Birlik Demirel, Gokcen; Aygul, Ebru; DAĞ, AYDAN; DAĞ, AYDAN; ATASOY, SEZEN; ATASOY, SEZEN; Cimen, Zeynep; Cetin, Busra (My University, 2020)
© 2020 American Chemical Society.Stimuli-sensitive and multifunctional nanoparticles are highly desirable biomedical materials for triggered and targeted drug delivery applications. Here, we have designed pH- A nd redox-triggered magnetic lipid-polymer hybrid nanoparticles (MHNPs) with a core-shell structure. This design is composed of a silica-/mesoporous silica-coated ellipsoidal magnetic nanoparticle with multifunctionality: Carrying the anticancer drug (doxorubicin, DOX), the cancer cell targeting ligand (folic acid-conjugated poly(ethylene glycol), FA-PEG) polymer, and being coated with a biocompatible pH-/redox-responsive (poly-l-histidine-poly(ethylene glycol)-lipoic acid; PLH-PEG-LA) polymer. The lipoic acid units of the PLH-PEG-LA shell of the FA-MHNPs were cross-linked using 1,4-dithiothreitol (DTT). When the FA-MHNPs-DOX were exposed to an endolysosomal pH of 5.5 and 10 mM glutathione (GSH), the particles exhibited a very efficient DOX release profile within 24 h. In addition, cytotoxicity, uptake, and apoptosis assays were performed against breast cancer cell lines. These results showed that FA-MHNPs-DOX promote an enhanced uptake and cell morbidity compared to the nontargeted MHNPs-DOX against tested cell lines. Moreover, the FA-MHNPs-DOX exhibited very effective cytotoxicity and also decreased the cell viability through apoptosis against breast cancer cell lines. In conclusion, it can be said that the pH and redox dual-responsive hybrid FA-MHNPs-DOX has a great potential for controlled drug release.